2004
DOI: 10.1063/1.1641184
|View full text |Cite
|
Sign up to set email alerts
|

Influence of three-dimensional transition elements on magnetic and structural phase transitions of Ni-Mn-Ga alloys

Abstract: Differential scanning calorimetry and magnetic measurements were performed to study the influence of the ferromagnetic three-dimensional transition elements Fe and Co on the structural and magnetic properties of the ferromagnetic shape memory alloys Ni-Mn-Ga. Substitution of Fe or Co for Ni decreases the temperature of martensitic phase transition Tm, whereas substitution of Co for Mn results in a considerable increase of Tm. Magnetic measurement revealed that Curie temperature TC increased upon substitution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A series of Heusler alloys Ni 55Àx Co x Mn 20 Ga 25 (x ¼ 0, 2, 4,6,8,10,12,15,18) were fabricated by arc melting 99.9% pure metals of Ni, Co, Mn, and Ga in argon atmosphere. The as-cast ingots were annealed at 1173 K for 24 h in evacuated quartz tubes and subsequently quenched into room temperature water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A series of Heusler alloys Ni 55Àx Co x Mn 20 Ga 25 (x ¼ 0, 2, 4,6,8,10,12,15,18) were fabricated by arc melting 99.9% pure metals of Ni, Co, Mn, and Ga in argon atmosphere. The as-cast ingots were annealed at 1173 K for 24 h in evacuated quartz tubes and subsequently quenched into room temperature water.…”
mentioning
confidence: 99%
“…7,8 It was considered that the decrease of T M stems from the decrease of the electron concentration e/a by the replacing Ni with Co. 7 The increase of the T C is suggested to relate with the higher magnetic moment of Co than that of Ni and stronger exchange interaction of Co-Mn as compared with Ni-Mn. 8 When the Co content is above the critical value x c , the martensitic transition of the system is completely suppressed and replaced by the strain glass transition. However, the ferromagnetic transition temperature T C increases further to higher temperature with increasing Co doping.…”
mentioning
confidence: 99%
“…9,10 However, T C in Ni-Mn-Ga alloys does not strongly depend on the composition and has a value of around 370 K for a wide range of compositions close to Ni 2 MnGa. 9,10 Cherechukin et al 11 found that a small amount of substitution of Co for Ni in Ni-Mn-Ga alloys increases T C and decreases T M slightly. Thus substitution of Co for Ni in the high-temperature Ni-Mn-Ga alloys can produce ferromagnetic Ni-Mn-Ga-Co alloys with high T C close to T M , by which a coupled magnetostructural transition may be realized and show great attractions in the development of alloy systems.…”
Section: Introductionmentioning
confidence: 97%
“…However, the change in T c with composition deviation is less significant and the temperature range is relatively narrow (340~390 K) [154]. Some fourth elements can influence T c more effectively [138,[154][155][156][157][158][159]: T c increases when Ni is substituted by either Fe or Co, and decreases with the substitution of Mn for V or Ga. As for the magnetic properties, the effects of chemical composition on the magnetic anisotropy constant are briefly mentioned in sec. 2.1.2.…”
Section: Composition and Electron Concentrationmentioning
confidence: 99%